Association between intestinal helminthic infections and anaemia status in preschool children in the district Skardu of Pakistan - Muhammad Faisal Afridi; Kulsoom Farhat; Zaheer Ahmed; Hajra Ahmed; Shabana Ali; Mehwish Nawaz Qaisrani (Journal of the Pakistan Medical Association, 2021)
Objective: This study has been aimed to evaluate the prevalence of parasitic infections and evaluate the correlation between intestinal helminth infection and the anemia status of pre-school children in the District Skardu of Pakistan. Methodology: A community-based, descriptive, cross-sectional analysis was carried out on 300 pre-school children of the district of Skardu. Demographical data was obtained through the structured questionnaire. The stool sample was collected and examined for intestinal parasites at pathology department of healthcare facility in Skardu. Blood Hemoglobin (Hb) was measured from blood sample and anemia was defined as blood Hb <11 g/dL. The data was analyzed using SPSS. Results: Out of a total of 300 children, 161 (i.e. 53.67%) were found infected and 139 (i.e. 46.33%) were found to be infection free. The overall parasite prevalence was: Ascaris Lumbricoides (22.33%), Cryptosporidium (14%) and Hymenolepis Nana and Giardia (9.3% and 8%) respectively. The 20% preschool children infested with Ascaris Lumbricoides, 13.7% infested with Cryptosporidium, 8.0% and 7.7% infested with Giardia and Hymenolepis Nana were mostly anemic. 15.3% preschool children with no parasite infestation were also found anemic. Conclusion: There is a high prevalence of these parasitic infections in the pre-school children in Skardu, where they also present with anemia. If there is a realization that these infections effect the Hb levels, then intervention programs be conducted, bringing more awareness about their control and advocating iron supplementation. Continuous....